The design of brake fluid filling unit / Rahim Atan - Atan, Rahim (1984)
The brake system is one of the most important parts in vehicles. It is extremely essential to leakage and contamination by moisture and air bubbles. The presence of air bubbles in the brake system will lead to ineffective braking air is compressible. One who drive a car without knowing the condition of the vehicles brake may endanger one’s life.